2023
DOI: 10.1039/d3cp00348e
|View full text |Cite
|
Sign up to set email alerts
|

Halogen bonds with carbenes acting as Lewis base units: complexes of imidazol-2-ylidene: theoretical analysis and experimental evidence

Abstract: The ωB97XD/aug-cc-pVDZ and ωB97XD/aug-cc-pVTZ calculations were performed on complexes of imidazol-2-ylide that are linked by halogen bonds. This singlet carbene acts as the Lewis base through lone electron pair located...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Then, Del Bene et al [94] performed theoretical studies of the halogen bond between ClCCH, ClCN, ClNC, or ClF and some rather exotic small carbenes. Quite recently, Grabowski performed calculations for imidazol-2-ylidene complexes with XCCH, XCN, and X 2 (X = F, Cl, Br, I) [95]. As might be expected, the F molecules did not form a halogen bond to the carbene carbon atom.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Then, Del Bene et al [94] performed theoretical studies of the halogen bond between ClCCH, ClCN, ClNC, or ClF and some rather exotic small carbenes. Quite recently, Grabowski performed calculations for imidazol-2-ylidene complexes with XCCH, XCN, and X 2 (X = F, Cl, Br, I) [95]. As might be expected, the F molecules did not form a halogen bond to the carbene carbon atom.…”
Section: Introductionmentioning
confidence: 93%
“…However, the characteristics of the relationship between H C•••X and d C•••X cause that with the decrease in the distance C• • • I, the value of H C•••X decreases rapidly, becoming a significantly negative number, which indicates a significant covalent contribution of the interaction. In extreme cases, an [IR 2 X] + [D] − ionic pair may be formed [95].…”
Section: Relationships Between Physical Quantitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…9 One can also mention a recent study on halogen bonds that link imidazol-2-ylidene with XCCH, XCN and X 2 Lewis acid units (X = F, Cl, Br and I); the calculations on these complexes were performed at the ωB97XD/aug-cc-pVDZ and ωB97XD/aug-cc-pVTZ levels. 10 Electrostatic potentials, EPs, were analysed in a later study, 10 and it was found that halogen bonds occur between the positive EP sites, i.e. σ-holes, 11–14 of halogen centres and the negative EP C-centre of imidazol-2-ylidene species.…”
Section: Introductionmentioning
confidence: 99%
“…At the outset, the interaction of carbene with transition metal [2,[19][20][21] produced highly valuable complexes in organic, material, and organo-metallic chemistry. [2,3,6] In addition, carbene also engages with other intermolecular interactions such as hydrogen bonds, [16,[22][23][24][25][26] halogen bonds, [26][27][28][29][30][31] beryllium bonds, [8,[32][33][34][35] lithium bonds, [8,29,[36][37][38] triel bonds, [29,[39][40][41][42] magnesium bonds, [34,35,[43][44][45] chalcogen bonds, [46] and aerogen bonds. [47] These interactions occur due to a lone pair of electrons in the carbene carbon atom.…”
Section: Introductionmentioning
confidence: 99%